Report on the Clinical Observation of Hypervis, an Oral Homoeopathic Liquid for Hypertension & Allied Symptoms (Advancements in Homeopathic Research, 2023)
Hypertension, the persistent increase in the blood  pressure (BP) above the normal values, is a very  worrying public health problem. It causes high  morbidity and mortality globally. Pre-hypertension is  also a sub-clinical condition, but remains a public  health challenge. It is a major risk factor for  subsequent cardiovascular diseases. Although  defining hypertension is very difficult, but individual  patient risk only assess from severity of hypertension.  Appropriate intervention is needed to stop its  progression and other cardiovascular diseases. The  use of homeopathic remedies is rising in the modern  time especially in chronic diseases like hypertension  and is proved effective in various clinical practices.  In this clinical experiment, we have tried to conclude  that there might be significant improvement among  one group of patients suffering from different  symptoms due to pre-hypertension & hypertension by  administering combination homeopathic medicine,  Hypervis & there was negligible or no improvement  while using placebo doses on another group of  patients in over 3 months of intervention while both  the groups received standardized recommendations  for dietary and lifestyle modifications.
Keywords: Homeopathy; hypertension; blood pressure